Urban Home Gardens Enhance Plant Diversity and Food Security in South Tangerang - Kristiyanto; Fahma Wijayanti (UIN Sunan Gunung Djati Bandung, 2026)
Achieving food security goals in urban settings has emerged as a major concern, as it is both essential and crucial to their ecological standing. To achieve food security through plant diversity, one approach is to actively and expertly use yards by growing a range of plants. This is one of the essential stages for supplying the fundamental needs of urban communities, both now and in the future. The purpose of this study is to describe the function of home gardens, their contribution to food availability and security, and strategies for diversifying them. With a quadrat sample size of 4×4 meters for trees and 1×1 meters for vascular understory vegetation, purposeful sampling is used to collect data. Vegetation analysis computes the diversity index (H') using the Shannon-Weiner method. Four (4) plant types are used in South Tangerang's yards: fruit (54%), vegetables (20%), medicinal (24%), and carbs (2%), according to the first research result. Thus, with H' values ranging from 3.015 to 3.028, the types of (food) crops in the Tangerang City region are categorized as high, with Pamulang District having the lowest value and Pondok Aren District having the highest. Therefore, growing a home garden contributes to the growth and preservation of urban plant species diversity within the community, as well as an alternative and innovative way to increase or expand food availability in a sustainable and ongoing manner.